A prospective cohort study on ambient air pollution, airborne pollen (and fungal spores) and respiratory morbidities including childhood asthma in adolescents from the Western Cape Province - Olaniyan, Toyib Adedamola (Department of Public Health and Family Medicine, 2019)
Background: The epidemiological studies investigating environmental risk factors associated with asthma among children living in informal settlements are scant as are studies on the independent and co-pollutant effect of short- and long-term exposures to ambient air pollutants as well as fungal spores on asthma-associated outcomes. This study systematically investigated these factors among schoolchildren residing in informal settlements in the Western Cape province of South Africa. Methods: A cohort study of grade-4 schoolchildren (n=590) recruited from six primary schools in four informal settlements was conducted over 12 months. In addition, a panel study, investigated the children for 2 consecutive school weeks in both summer and winter. Spirometry and fractional-exhaled nitric oxide (FeNO) measurements were conducted during the school day, while the International Study on Asthma and Allergy in Children (ISAAC) standardised questionnaire was administered to the parent or guardian at the child’s home at baseline and follow-up. The presence of atopy was determined based on a positive Phadiatop test on sera. In the cohort study, annual NO2 and PM2.5 levels were computed for each child’s address using a land-use regression model. Daily PM10 levels obtained from a stationary monitor near two of the study areas were used for the panel study. Airborne pollen and fungal spore measurements were obtained directly from a stationary monitor placed in each study area. Results: The prevalence of doctor-diagnosed asthma was 3.4% and only half of them were on asthma treatment. The prevalence of wheezing in the past 12 months (12.9%), airway obstruction (17.6%) and airway inflammation (10.2%) was much higher. The presence of damp conditions, visible mould growth, passive smoking as well as paraffin-use for cooking and heating were significant indoor risk factors for asthma. The estimated annual average NO2 level of 16.6 µg/m3 was below the WHO annual exposure standards, however more than a third of children were exposed to annual PM2.5 levels above the 10 µg/m3 WHO standard and the allergic symptom threshold level of 100 spores/m3 for Alternaria spores. In the panel study, daily exposure of schoolchildren to Alternaria and Cladosporium spores independently decreased FEV1 (-27.56 ml, 95% CI: -50.60 to -4.51 ml per 10 spores/m3 increase in Alternaria; and -86.19ml, 95% CI: -131.69 to -40.70 ml per 50 spores/m3 increase in Cladosporium respectively) from lag day-0 to lag day-5, especially in the winter monitoring period. In the cohort study, an interquartile range increase of 14.2 µg/m3 in annual NO2 was associated with an risk of new onset ocular-nasal symptoms (adjusted odds ratio – aOR: 1.63, 95% CI: 1.01 – 2.60), wheezing (aOR: 3.57, 95% CI: 1.18 – 10.92), more than two or more asthma symptom score (aOR: 1.71, 95% CI: 1.02 – 2.86), and airway inflammation defined as FeNO > 35ppb (aOR: 3.10, 95% CI: 1.10 – 8.71), independent of PM2.5 exposures. In addition, an interquartile increase of 83.1 spores/m3 in 24-hour annual Alternaria spore levels was associated with an increased risk of airway inflammation incidence and having a ≥ 10% increase in FeNO at follow-up both in the single-pollutant model and two-pollutant model. Conclusion: This study demonstrated a large proportion of undiagnosed and untreated asthma in schoolchildren living in informal settlements, with both indoor and outdoor mould exposures playing an important role in addition to ambient chemical pollutants. The incidence of new onset asthma symptoms and airway inflammation associated with NO2 at levels below the WHO Air Quality Standards raises the issue of the adequacy of these standards in protecting respiratory health. Raised long-term levels of airborne Alternaria spores contributing to increased airway inflammation is likely to form the basis for the increased risk of acute symptoms and airway effects observed in association with exposure peaks.